EFEKTIVITAS PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KANTOR PERTANAHAN KABUPATEN MOJOKERTO - Fladyo Pratama; Shal Aysa Gladis Rahma Dwi Nada; Mufarrijul Ikhwan (Jurnal Jendela Hukum, 2026)
The Complete Systematic Land Registration Programme aims to accelerate land certification and provide legal certainty forthe community. However, the implementation of PTSL in Mojokerto Regency has not beenoptimal, especially at the document verification stage, which is an important partbefore the issuance of certificates. This study found that many applicant filesdid not meet administrative requirements, such as invalid land history,statements of physical control without witnesses, outdated SPPT (Land and Building Tax Assessment Notices),inconsistent identity data, and incomplete minutes and official reports. This situation requires officers to conduct additional verifications, thereby slowing down the service process and not complying with the principles of speed andsimplicity as stipulated in ATR/BPN Ministerial Regulation No. 6 of 2018. These findings indicate that the effectiveness of PTSL implementation is greatlyinfluenced by the administrative readiness of the community and the verification mechanism at theland office.